Why mixotrophy flourished in water but rarely on land - Calbet, Albert (Frontiers in Ecology and Evolution, 2026)
Mixotrophy, the ability to combine photosynthesis with heterotrophic acquisition of carbon or nutrients, is now recognized as a central feature of aquatic microbial food webs and a recurrent strategy in several protist and simple animal lineages. By contrast, terrestrial ecosystems host only a narrow set of mixotrophic plants, and no animal is known to rely substantially on endogenous photosynthesis or plastids over its life cycle. Here I argue that this asymmetry is not paradoxical once mixotrophy is viewed through three coupled filters: ecological state spaces, evolutionary accessibility and physiological feasibility. I outline how these filters differ between water and land, how they jointly compress the adaptive zone for mixotrophy after terrestrialization, and how they generate explicit, testable predictions for future empirical and theoretical work on dual nutritional strategies.